Roald Dahl Little Library. 3, Numbers - Dahl, Roald; Blake, Quentin, 1932- (London : Puffin Books, 2019)
ONE enormous crocodile, TWO little mice, THREE mischievous monkeys . . .Learn whizzpopping numbers, splendiferous colours, glorumptious opposites, and meet phizz-whizzing creatures from the world of Roald Dahl. A delightful treat for curious little hands, this little library is perfect for introducing titchy toddlers to new concepts, and to the imaginative world of Roald Dahl.
Part from the Roald Dahl Little Library (3 from 4) - Numbers
Keywords: leporelá; cudzojazyčná literatúra; čítame si spolu 0+